The Programme of Forming Future Music Art Teachers’ Ethnic and Cultural Competence - Solyar, Larysa (Pedagogical Discourse, 2017)
The author’s program of forming future music art teachers’ ethnic and cultural competence has been brought out in the article. Two blocks of the programme – theoretical and methodical (professional and cognitive, ethnic and cultural planes) and practical and effective (personal and motivational, operational and reflective planes) have been presented. Professional and cognitive plane is responsible for learning the history of culture and its development in various ethnic and regional groups; for creative thinking and implementation of professional competence aimed at the formation of ethnic and cultural competence into the professional activities. Ethnic and cultural plane stipulates learning rich culture, huge treasure of which consists of priorities and values, gained by many generations. Personality and motivational plane reflects orientation of educational activities and, by relying on the system of interrelated concepts, provides and supports the process of the personality’s self-knowledge, self-identity, development of the people’s ethnic culture. Operational and reflective plane charges the system of competences related to educational activities; formation of the tasks of ethnic and cultural competence and learning its contents. The author’s elective course « Future music art teachers’ ethnic and cultural competence», providing formation of ethnic and cultural competence combined with humanitarian disciplines that systematize the knowledge of ethnic and cultural competence, national values, traditions, rituals and customs, has been determined as the basis for the realization of the author’s programme. The prospects for further scientific research, defined in the article, are to develop methodological tools, namely: methods, forms and means of forming future music art teachers’ ethnic and cultural competence. Key words: ethnic and cultural competence, programme, blocks, planes music art.